(untitled) (MMIT Proceedings, 2024)
This article explores the role of motivation and self-regulation in contemporary pedagogy and strategies for stimulating learning activity. It examines the theoretical foundations of motivation and self-regulation, their impact on the learning process, and student success. Internal and external factors influencing motivation and self-regulation are analyzed, and various strategies to enhance them are proposed. Special attention is given to the use of modern technologies such as educational platforms, gamification, virtual and augmented reality, to create a personalized and motivating learning process. Practical aspects of implementing these strategies in the educational environment are described. The conclusion emphasizes the importance of developing motivation and self-regulation to improve learning activity and student achievement, and the need for further research and innovation in this area.